Proteomic and Phosphoproteomic Maps of Lung Squamous Cell Carcinoma From Chinese Patients - Pan, Lulu; Wang, Xijun; Yang, Longhai; Zhao, Lei; Zhai, Linhui; Xu, Junyu; Yang, Yikun; Mao, Yousheng; Cheng, Shujun; Xiao, Ting; Tan, Minjia (Frontiers in Oncology, 2020)
Lung squamous cell carcinoma (LUSC) is one of the leading causes of tumor-driven deaths in the world. To date, studies on the tumor heterogeneity of LUSC at genomic level have only revealed limited therapeutic benefits. Therefore, system-wide research of LUSC at proteomic level may further improve precision medicine strategies on individual demands. To this end, we performed proteomic and phosphoproteomic study for LUSC samples of 25 Chinese patients. From our results, two subgroups (Cluster I and II) based on proteomic data were identified, which were associated with distinct molecular characteristics and clinicopathologic features. Combined with phosphoproteomic data, our result showed that spliceosome pathway was enriched in Cluster I, while focal adhesion pathway, immune-related pathways and Ras signaling pathway were enriched in Cluster II. In addition, we found that lymph node metastasis (LNM) was associated with our proteomic subgroups and cell cycle pathway was enriched in patients with LNM. Further analysis showed that MCM2, a DNA replication licensing factor involved in cell cycle pathway, was highly expressed in patients with poor prognosis, which was further proved by immunohistochemistry (IHC) analysis. In summary, our study provided a resource of the proteomic and phosphoproteomic features of LUSC in Chinese patients.